Family dyads, emotional labor, and holding environments in the simulated encounter: co-constructive patient simulation as a reflective tool in child and adolescent psychiatry training - Isaiah Thomas; Laelia Benoit; Robbert Duvivier; Marco Antonio de Carvalho Filho; Andrés Martin (BMC, 2023)
Abstract Background Patient simulation has been used in medical education to provide a safe and supportive learning environment for learners to practice clinical and interpersonal skills. However, simulation involving pediatric populations, particularly in child and adolescent psychiatry, is rare and generally does not reflect the child-caregiver dyad or the longitudinal aspects of this care, nor does it provide learners with an opportunity to engage with and reflect on these dynamics. Methods We organized as an educational opportunity a series of seven observed patient simulation sessions with a cohort of a dozen child and adolescent psychiatrists (eight fellows approaching graduation and four senior educators). In these sessions, we utilized the co-constructive patient simulation model to create the simulation cases. We included the use of at least two patient actors in most sessions, and two of the case narratives were longitudinally followed across multiple simulation sessions. We approached the data collected during the simulations and their respective debriefings by using thematic analysis informed by a symbolic interactionist approach. Results Based on data from the debriefing sessions and longitudinal narratives, we identified four overarching themes: (1) Reflecting on dyadic challenges: role reversal and individuation; (2) Centering the child, allying with the parent, and treating the family system; (3) Ambivalence in and about the parent-child dyad; and (4) Longitudinal narratives and ambivalence over time. Conclusion The emotional experience of the simulations, for interviewers and observers alike, provided an opportunity to reflect on personal and professional experiences and triggered meaningful insights and connections between participants. These simulated cases called for emotional labor, particularly in the form of creating holding environments; in this way, the simulated encounters and the debriefing sessions became dialogic experiences, in which the patient and provider, parent and child, and learner and instructor could co-construct meaning and foster professional development as reflective practitioners.